Obit : poems - Chang, Victoria, 1970- (Copper Canyon Press, 2020)
After her mother died, poet Victoria Chang refused to write elegies. Rather, she distilled her grief during a feverish two weeks by writing scores of poetic obituaries for all she lost in the world. In this book, she writes of "the way memory gets up after someone has died and starts walking." These poems reinvent the form of newspaper obituary to both name what has died ("civility," "language," "the future," "Mother's blue dress") and the cultural impact of death on the living. Whereas elegy attempts to immortalize the dead, an obituary expresses loss, and the love for the dead becomes a conduit for self-expression. In this unflinching and lyrical book, the poet meets her grief and creates a powerful testament for the living. --